Βτ1, τ2-Continuous Multifunctions on Bitopological Spaces. (22nd January 2020) - Laprom, Kaewta; Boonpok, Chawalit; Viriyapong, Chokchai
Abstract : The purpose of this paper is to introduce the concepts of β τ 1, τ 2 -continuous multifunctions and almost β τ 1, τ 2 -continuous multifunctions. Moreover, some characterizations of β τ 1, τ 2 -continuous multifunctions and almost β τ 1, τ 2 -continuous multifunctions are investigated.